Eksplorasi Dampak Sistem Manajemen Pembelajaran Terhadap Proses Pembelajaran: Wawasan Respon Mahasiswa Prajabatan PPG - Abdul Wahid; Sukri Syamsuri, Andi; Nasrun, Nasrun; Mulawakkan, Andi; Dahlan, Muhammad (Universitas Pendidikan Ganesha, 2024)
The use of LMS in the learning process of PPG Pre-service students has not yet been widely researched. This research aims to analyze and explain the responses of Pre-Service PPG students at Muhammadiyah University of Makassar towards the use of the Learning Management System (LMS) in the learning process. This research is categorized into qualitative descriptive research. A total of 42 Pre-Service Teacher Professional Education (PPG) students participated in this research. Data was collected through questionnaires and unstructured interviews, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of this research show that student responses come from four categories, namely experience using LMS, benefits and advantages of LMS, challenges faced, and understanding of the material. The majority of students stated that the LMS made a significant contribution to understanding the learning material, most of them rated the LMS as a tool that was “very helpful” or “helpful” in the learning process. This research also shows that the main challenges faced are related to accessibility, especially in terms of networks and limited internet access. The implications of these findings include the need to improve technology infrastructure, increase support, and train students and lecturers in using the LMS. Apart from that, the integration of technology in the higher education curriculum is also an important aspect that needs to be considered.